CARMIL2 Deficiency Presenting as Very Early Onset Inflammatory Bowel Disease. Issue 11 (22nd May 2019) - Magg, Thomas; Shcherbina, Anna; Arslan, Duran; Desai, Mukesh M; Wall, Sarah; Mitsialis, Vanessa; Conca, Raffaele; Unal, Ekrem; Karacabey, Neslihan; Mukhina, Anna; Rodina, Yulia; Taur, Prasad D; et al.
Abstract: Background: Children with very early onset inflammatory bowel diseases (VEO-IBD) often have a refractory and severe disease course. A significant number of described VEO-IBD-causing monogenic disorders can be attributed to defects in immune-related genes. The diagnosis of the underlying primary immunodeficiency (PID) often has critical implications for the treatment of patients with IBD-like phenotypes. Methods: To identify the molecular etiology in 5 patients from 3 unrelated kindred with IBD-like symptoms, we conducted whole exome sequencing. Immune workup confirmed an underlying PID. Results: Whole exome sequencing revealed 3 novel CARMIL2 loss-of-function mutations in our patients. Immunophenotyping of peripheral blood mononuclear cells showed reduction of regulatory and effector memory T cells and impaired B cell class switching. The T cell proliferation and activation assays confirmed defective responses to CD28 costimulation, consistent with CARMIL2 deficiency. Conclusion: Our study highlights that human CARMIL2 deficiency can manifest with IBD-like symptoms. This example illustrates that early diagnosis of underlying PID is crucial for the treatment and prognosis of children with VEO-IBD. Abstract : Patients with inherited CARMIL2 deficiency can present with pediatric inflammatory bowel disease. Early diagnosis of the underlying primary immunodeficiency has critical implications for the clinical management of affected children.